A Novel CC-Chemokine Receptor 3 Antagonist, Ki19003, Inhibits Airway Eosinophilia and Subepithelial/Peribronchial Fibrosis Induced by Repeated Antigen Challenge in Mice - Masato Komai; Hiroyuki Tanaka; Koichi Nagao; Masayuki Ishizaki; Daisuke Kajiwara; Toru Miura; Hiroshi Ohashi; Tomoko Haba; Kazuki Kawakami; Eiji Sawa; Osamu Yoshie; Naoki Inagaki; et al. (Elsevier, 2010)
CC-chemokine receptor 3 (CCR3) is a chemokine receptor for which major ligands, CC-chemokine ligand (CCL) 11, CCL24, and CCL26, are known to be involved in chemotaxis for eosinophils. In the present study, we evaluated the effect of a low molecular weight CCR3-receptor antagonist, Ki19003 (4-[[5-(2,4-dichlorobenzylureido)pentyl][1-(4-chlorophenyl)ethyl]amino]butanoic acid), on airway remodeling in a mouse model of allergic asthma. BALB/c mice were sensitized twice by intraperitoneal injection of ovalbumin (OA) and exposed daily to 1% OA for 3 weeks. Twenty-four hours after the final antigen challenge, bronchoalveolar lavage and histological examinations were carried out. Ki19003 clearly inhibited antigen-induced increase in the number of eosinophils in bronchoalveolar lavage fluid (BALF), but did not affect the number of other cell types examined in this study. Ki19003 also inhibited the increased production of transforming growth factor-β1 in BALF and the amount of hydroxyproline in the lungs in a dose-dependent manner. Furthermore, Ki19003 significantly attenuated allergen-induced subepithelial and peribronchial fibrosis. These findings indicate that CCR3 antagonism prevents not only the infiltration of eosinophils into the airways but also the development of allergen-induced subepithelial and peribronchial fibrosis. Therefore, a CCR3 antagonist may be useful in the treatment of airway remodeling, especially subepithelial and peribronchial fibrosis, in allergic asthma. Keywords:: asthma, eosinophil, eotaxin, subepithelial fibrosis, transforming growth factor-β1